STUDENT SATISFACTION IN ONLINE LEARNING TOWARDS LEARNING OUTCOMES IN BASIC TEACHING ABILITY COURSES - Renny Thereesje Tumober; Febriani Safitri (Program Magister Pendidikan IPA, Program Pascasarjana Universitas Cenderawasih, 2022)
This study aims to determine, 1) The relationship between student satisfaction in online learning and student learning outcomes in basic teaching skills courses, 2) the effect of student satisfaction in online learning on student learning outcomes in basic teaching skills courses, odd semester of the academic year 2021/ 2022. This research was conducted in October - November 2021. The subjects in this study were all students who contracted 27 students' basic teaching skills courses and the objects of research were student satisfaction and student learning outcomes. The instruments used are questionnaires and tests. Data analysis was performed using the Pearson correlation test with a significance level of 0.05 and a regression test which resulted in conclusions as a result of the study. To find out whether or not there is a relationship and influence of each variable, the research data is processed using SPPS version 16. The results show that, there is a significant relationship between student satisfaction in online learning and student learning outcomes in the basic teaching ability subject in the medium category, and there is an effect of student satisfaction on online learning on student learning outcomes in the basic teaching ability course, by contributing 24.5%.